A study on depression, anxiety, and stress scale according to status and gender among Islamic shelter care residents in Terengganu, Malaysia - Siti Hajar, Abdul Rauf; Hidayatul Najihah, M.Z.; Nur Adilla, A. (2019)
Objective: The aim of this study is to identify depression, anxiety, and stress symptoms on status and gender among the residents of Islamic Care Shelter in Terengganu, Malaysia. 198 residents of 9 Islamic Care Shelter's institutions was used as a sample. Methods: Principal Component Analysis (PCA) was used in this research to revealed multilateral dominant variables for the residents. Meanwhile, the other method had been used is Multivariate Analysis of Variance (MANOVA) to discover the significance of independent variables which is status and gender. Result: PCA showed that there was 6 factor dominant that contribute to DASS questionnaire. For MANOVA, the result showed that there was difference significant interaction effect between status and gender. For the categorical status between orphan and non-orphan showed the value of significant is 0.023 and for gender is 0.001. These both proved that p-value is less than 0.05. Conclusion: We recommend that the further study about DASS need to be more widely distributed among the marginalized group.